Climate change and urban thermal stress: spatial-temporal analysis of bioclimatic comfort in Bursa, Türkiye - Canturk, U.; Koc, I.; Aricak, B. (Springer, 2025)
Climate change is reshaping global environmental dynamics, with profound implications for urban livability. This study evaluates long-term bioclimatic comfort shifts in Bursa, T & uuml;rkiye-a key industrial and agricultural region-using Discomfort Index (DI) and Effective Temperature-taking wind velocity (ETv) techniques under SSP2-4.5 (middle-of-the-road development) and SSP5-8.5 (fossil fuel-based development) scenarios (2022-2100). Model validation via AUC-ROC demonstrated robust accuracy for both indices (DI: 0.679-0.704; ETv: 0.602-0.654), confirming their reliability in projecting spatial-temporal changes. Results indicate a pronounced warming trend, with Bursa transitioning from cool to warm bioclimatic zones: by 2100, 62.9% (SSP2-4.5) to 69.1% (SSP5-8.5) of the province will shift into warmer comfort classes per DI, while ETv projects expanding very hot zones (8.5% under SSP5-8.5). Concurrent humidity declines (up to 4-6% reduction by 2100) will exacerbate thermal stress, particularly in urbanized areas. Projected changes will significantly increase cooling energy demands and public health risks, demanding urgent climate adaptation in urban planning. Our transferable methodology provides actionable insights for enhancing heat resilience and sustainable infrastructure in vulnerable Mediterranean cities. Overall, the findings emphasize the necessity of integrating thermal comfort concerns into regional development policies to mitigate escalating climate risks.
Keywords: AUC-ROC validation; Urban planning; Spatial modelling; Thermal comfort indexes